Keutamaan Ilmu Sebagai Fondasi Dalam Membangun Peradaban Islam Di Era Modern: Perspektif Nilai Dan Relevansi Kontemporer - Halimatus Syakdiyah; Ainur Rofiq Sofa; Muhammad Sugianto (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
The supremacy of knowledge plays a central role in building Islamic civilization, both in classical and modern eras. This study aims to analyze the values of the supremacy of knowledge based on the perspectives of the Qur’an, Hadith, and the thoughts of classical scholars such as Al-Ghazali, Ibn Khaldun, and Al-Farabi. Additionally, this research explores the relevance of knowledge in addressing the challenges of globalization and the dynamics of the digital age. Using a descriptive qualitative research method, primary data consisting of Qur'anic verses, Hadith, and classical scholars' works are combined with secondary data, including books on the history of Islamic civilization, scholarly articles, and contemporary references. The research findings indicate that knowledge is regarded as the main pillar in building a civilization rooted in Islamic values. The Qur’an and Hadith explicitly position knowledge as both an obligation and a path to the glory of individuals and society. The thoughts of classical scholars highlight the importance of integrating religious knowledge and general knowledge to create a balance between worldly and spiritual happiness. In the modern era, the supremacy of knowledge remains relevant as a tool to address the challenges of globalization, particularly through the use of technology and innovation based on Islamic values. This study concludes that the synergy between religious knowledge and modern science can shape a progressive and morally upright Islamic civilization. Knowledge not only serves as a medium for social transformation but also as a spiritual foundation for building a resilient Muslim identity in the contemporary era. The relevance of the values of the supremacy of knowledge provides a strategic guide for Muslims to contribute to global civilization without losing the essence of Islam.